Peranan Mahasiswa Kukerta Unri 2022 dalam Pemberdayaan UMKM Ikan Salai di Kelurahan Tobekgodang - Davit Rahmadan; Andra Febriona Putri; Arief Setiawan; Dian Dharmayanty; Islah Hidayat Ritonga; Nurkamila Rahmadini; Salsabila Briana Wijaya; Shintya Aulya Putri; Siti Haviza Prada Lopi; Suci Awalyah Putri; Zahara Nurmakassing (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2022)
Smoking is a method of processing fish by utilizing smoke from the combustion of wood which can provide a distinctive aroma, color, and taste. Salai fish is a type of traditional Indonesian smoked fish that is easy to find among the public. In Indonesia itself, Riau Province is one of the largest salai fish producing areas and is an area that is famous for the quality of salai fish. In Tobekgodang Village, Binawidya Subdistrict, Pekanbaru City, there is a production house of smoked fish which is famous for its smoked catfish which has been exported abroad. The smoked fish production house owned by Mr. Hawari Umar is one of the MSME sectors that produces superior products for Tobekgodang Village. The smoked fish produced by Mr. Hawari Umar's production house is catfish (Clarias sp.) because this fish belongs to the type of freshwater fish that is widely breed in Indonesia, especially in Riau. Some benefits of the catfish is having good fats, reducing the risk of chronic disease, having lots of protein, and much more.